PENGARUH KUALITAS PRODUK, HARGA PRODUK, DAN KEMASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA JUS BUAH DEPOT SALMON DI SURABAYA - Vachel, Jovi; Radianto, Wirawan ED (Jurnal Performa: Jurnal Manajemen dan Start-up Bisnis, 2021)
This research is based on the failure of researchers' business namely Carico, Carico is a company engaged in the Food and Baverage industry, Carico is one of the original local brands of Indonesia, which sells authentic Carica fruit juice, Carica fruit can only grow in 2 places in the world. Carica fruit juice with a sweet and fresh taste has many health benefits, such as smooth digestion. However, as the sales process in Carico fluctuated, the researchers wanted to benchmark with similar competitors. Researchers use Salmon Depot Juice as a benchmarking in this study because the Salmon Depot Juice business is much better profit. Jus Depot Salmon was established in 2016 at Ciputra University in Surabaya. Prices offered by Salmon Depot juice range from IDR 10,000 - IDR 20,000. Salmon Depot Juice uses one employee and sells a variety of juice variants. In one day, it can sell 100 to 150 cups with a turnover of Rp 1,000,000 to Rp 2,000,000. Consumers who buy are Ciputra University students. The formulation of the problem in this study is whether the quality, price, and packaging of the product affect the purchasing decision of salmon depot fruit juice products in Surabaya. That is expected to be input for researchers in making improvements and adding insights about purchasing decisions, product quality, product prices and product packaging in running a food and beverage industry business. Researchers used quantitative methods with a population of consumers who bought Salmon Depot juice products in Surabaya with an infinite amount, using 385 people taken from the formula according to (Sugiyono, 2018; 142). The data collection method uses an offline questionnaire using a Likert scale and uses multiple linear regression analysis. The results of this study are the quality, price and product packaging significantly influence purchasing decisions. Keywords: product quality, product prices, product packaging, purchasing decisions.